ADOPTION OF INTERNATIONAL EDUCATION POLICY IN INDONESIA: Impact to Teacher Education and Professional Development - Zen, Satia Prihatni (Sukma: Jurnal Pendidikan, 2018)
The paper discussed the implication of adopting international education policy in Indonesia through international development aid and funding. Specific implications to teacher education and teacher professional development was discussed by analyzing two education reforms enacted in 1980 to 1990’s. The paper describes implementation processes and challenges faced by the programs from local dynamics especially on how social, political and historical influence teacher identity as well as teaching culture. The implications to school, district as well as national policy was discussed in light of uniformity of educational system by dissemination of best practices and model of education through aid and other cooperative projects. Local responses to international education policy is increasingly relevant to ensure education reform will respond local needs and sensitive to local context.Artikel ini mendiskusikan implikasi dari mengadopsi kebijakan international di Indonesia melalui dana dan bantuan international. Khususnya, dampak pada pendidikan guru dan perkembangan professional guru dikaji melalui dua program pendidikan yang diterapkan pada tahun 1980-an hingga 1990-an. Deskripsi dari pelaksanaan dan tantangan yang dihadapi dalam implementasi program tersebut dilihat dari konteks local dimana pengaruh social, politik dan sejarah mewarnai konsepsi identitas guru serta budaya pengajaran di sekolah. Implikasi pada kebijakan sekolah, pemerintah local dan nasional dimana kecenderungan akan penyeragaman system pendidikan terjadi melalui kerjasama dan bantuan juga dijabarkan. Artikel ini menekankan pentingnya respon local yang relevan terhadap penerapan kebijakan pendidikan internasional agar sensitive terhadap kebutuhan dan konteks local itu sendiri.